DESAIN DAN IMPLEMENTASI SISTEM INFORMASI PENILAIAN PELAYANAN PROSES BELAJAR MENGAJAR DI STMIK YADIKA BANGIL - Panca Rahadianto; Fikry Firmansyah (SPIRIT, 2016)
In the world of education, especially higher education active role as a teacher is very important in the teaching learning process . Lecturer is a major cornerstone in the transformation of science given by the university to its students . Therefore STMIK Yadika Bangkil as one of the colleges in Bangkil always working to improve the quality of the faculty as one of the most important factors in the learning process . STMIK in support of the information technology can be used to meet the needs of faculty performance quality information , in this case the quality of the information obtained from the evaluation of faculty performance is assessed performance of student teachers . Therefore this study aims to generate an Application -Based Performance Evaluation Lecturer titled Web Sistm Rating Information Services of Teaching and Learning In STMIK Yadika using the programming language PHP , MySql database and using Waterfall Modeling methodology . Expected results of this research in the form of application performance evaluation can help STMIK Yadika in terms of improving the quality of lecturers